2020
DOI: 10.4187/respcare.07720
|View full text |Cite
|
Sign up to set email alerts
|

2019 Year in Review: Neonatal Respiratory Support

Abstract: Respiratory support of the critically ill neonate has steadily shifted from invasive to noninvasive forms of support. There have recently been a number of important advances in our understanding of the changes to neonatal resuscitation practices as they pertain to clinically important outcomes, mechanisms of gas exchange for high-flow nasal cannula, and best use of noninvasive ventilation and predicting response. Although the proportion of infants requiring intubation and mechanical ventilation has decreased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 90 publications
0
16
0
4
Order By: Relevance
“…Other parameters than humidity and flow rate (2 L/min), such as temperature, air composition and oxygen content, were not studied. Moreover, oxygen therapy via an oxygen cannula does not accurately represent the most invasive and non-invasive respiratory equipment used in a NICU (Wheeler & Smallwood, 2020).…”
Section: Respiratory Supportmentioning
confidence: 99%
“…Other parameters than humidity and flow rate (2 L/min), such as temperature, air composition and oxygen content, were not studied. Moreover, oxygen therapy via an oxygen cannula does not accurately represent the most invasive and non-invasive respiratory equipment used in a NICU (Wheeler & Smallwood, 2020).…”
Section: Respiratory Supportmentioning
confidence: 99%
“…Despite a recent shift from invasive forms to noninvasive ones, RS is still a prevalent procedure in VLBW neonates. 33 The work of breathing as a measure of energy expenditure may be as high as 6-fold in an infant with respiratory distress, a typical case in VLBW neonates, compared with normal infants. 26 Assuming that accelerating weight through increasing administered calories can compensate energy expenditure for neonates' work of breathing, the authors hypothesized that the duration of RS in the experimental group would be significantly lower than that of the control group (Hypothesis 2).…”
Section: Duration Of Respiratory Supportmentioning
confidence: 99%
“…The use of invasive mechanical ventilation (IMV) via an endotracheal tube, in addition to other interventions such as the use of exogenous surfactant 1 and antenatal steroids, 2 has contributed to improvement in neonatal survival. 3 However, the prolonged use of IMV may predispose infants to the development of various complications, including bronchopulmonary dysplasia. 4 , 5 Avoiding IMV is a goal in clinical care, 3 and different modes of non-invasive ventilation (NIV), such as high flow nasal cannula (HFNC), 6 nasal continuous positive airway pressure (NCPAP), 6 nasal intermittent positive pressure ventilation (NIPPV), 7 and its more advantageous form, synchronized nasal intermittent positive pressure ventilation (SNIPPV), 8 have been shown to decrease the rate of IMV.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, the prolonged use of IMV may predispose infants to the development of various complications, including bronchopulmonary dysplasia. 4 , 5 Avoiding IMV is a goal in clinical care, 3 and different modes of non-invasive ventilation (NIV), such as high flow nasal cannula (HFNC), 6 nasal continuous positive airway pressure (NCPAP), 6 nasal intermittent positive pressure ventilation (NIPPV), 7 and its more advantageous form, synchronized nasal intermittent positive pressure ventilation (SNIPPV), 8 have been shown to decrease the rate of IMV. For example, though not a feature explored in the current study, the use of SNIPPV has been demonstrated to have several benefits in preterm infants, including decreased work of breathing, 9 reduction in incidence of apnea of prematurity, 8 shorter duration of ventilation, 10 and reduction in death for very low birth weight infants.…”
Section: Introductionmentioning
confidence: 99%